Local atomic order and hierarchical polar nanoregions in a classical relaxor ferroelectric - M. Eremenko (Nature Portfolio, 2019)
The understanding of relaxor ferroelectrics is hindered by the complexity of nanoscale perturbations of their structure. Here, a data set of independent techniques treated on common footing provides a multiscale description of atomic order which reconciles conflicting models derived from single methods.